ECOTOURISM FOR CITY BRANDING STRATEGY: PERSPECTIVE FROM FIVE CITIES IN INDONESIA - Mihardja, Eli Jamilah; Widiastuti, Tuti; Agustini, Prima Mulyasari; Bintoro, B.P. K (International Journal of Psychosocial Rehabilitation, 2020)
Ecotourism could be a program that can support sustainable development. Ecotourism can be an effort to maintain and increase participation of nature conservation and the welfare of local residents. However, ecotourism as a city branding rarely been found. This research explores the potential opportunities for ecotourism as a city branding strategy. Data was collected by document analysis, in-depth interviews, focus group discussions, as well as the observation of the five cities in Indonesia in the period 2018-2019. The results showed that despite having unique and abundant natural potential, ecotourism was not chosen as a priority to be developed as a city branding. There are obstacles to developing ecotourism and implementing it as a city branding strategy derived from the preferences of stakeholders and the practical interests of city managers.